Synthesis of Ultrahighly Electron-Deficient Pyrrolo[3,4-d]pyridazine-5,7-dione by Inverse Electron Demand Diels–Alder Reaction and Its Application as Electrochromic Materials - Ye, Qun (2016)
A new electron acceptor 6-alkylpyrrolo[3,4-d]pyridazine-5,7-dione (PPD) with a very low LUMO level has been synthesized via a challenging inverse electron demand Diels–Alder reaction between thiophene and furan-decorated tetrazine substrates and an electron-deficient 1-alkyl-1H-pyrrole-2,5-dione unit. The PPD monomer has been incorporated into a series of donor–acceptor-type conjugated polymers as electrochromic materials with good optical contrast, fast switching speed, and high coloration efficiency.